High-harmonic generation in Weyl semimetal β-WP2 crystals - Yang-Yang Lv (Nature Portfolio, 2021)
Weyl semimetals have interesting band-structure features that lead to unique properties. Here, the authors observe and study high-harmonic generation in type-II Weyl semimetal β-WP2 crystals.